Lowering Uric Acid With Allopurinol Improves Insulin Resistance and Systemic Inflammation in Asymptomatic Hyperuricemia. Issue 8 (December 2015) - Takir, Mumtaz; Kostek, Osman; Ozkok, Abdullah; Elcioglu, Omer Celal; Bakan, Ali; Erek, Aybala; Mutlu, Hasan Huseyin; Telci, Ozge; Semerci, Aysun; Odabas, Ali Riza; Afsar, Baris; Smits, Gerard; et al.
Abstract : Background: Hyperuricemia is an independent predictor of impaired fasting glucose and type 2 diabetes, but whether it has a causal role in insulin resistance remains controversial. Here we tested the hypothesis that lowering uric acid in hyperuricemic nondiabetic subjects might improve insulin resistance. Methods: Subjects with asymptomatic hyperuricemia (n = 73) were prospectively placed on allopurinol (n = 40) or control (n = 33) for 3 months. An additional control group consisted of 48 normouricemic subjects. Serum uric acid, fasting glucose, fasting insulin, HOMA-IR (homeostatic model assessment of insulin resistance), and high-sensitivity C-reactive protein were measured at baseline and at 3 months. Results: Allopurinol-treated subjects showed a reduction in serum uric acid in association with improvement in fasting blood glucose, fasting insulin, and HOMA-IR index, as well as a reduction in serum high-sensitivity C-reactive protein. The number of subjects with impaired fasting glucose significantly decreased in the allopurinol group at 3 months compared with baseline (n = 8 [20%] vs n = 30 [75%], 3 months vs baseline, P < 0.001). In the hyperuricemic control group, only glucose decreased significantly and, in the normouricemic control, no end point changed. Conclusions: Allopurinol lowers uric acid and improves insulin resistance and systemic inflammation in asymptomatic hyperuricemia. Larger clinical trials are recommended to determine if lowering uric acid can help prevent type 2 diabetes.